Nano and Microemulsions for the Treatment of Depressive and Anxiety Disorders: An Efficient Approach to Improve Solubility, Brain Bioavailability and Therapeutic Efficacy - Patrícia C. Pires; Ana Cláudia Paiva-Santos; Francisco Veiga (Pharmaceutics, 2022)
Most drugs used for the treatment of depression, anxiety and related disorders have low absorption, high metabolism, low brain targeting and/or low water solubility, which can make it hard to formulate them at high strength and can also lead to decreased bioavailability. Incorporating these drugs into nanometric emulsions can solve these issues. Hence, the aim of the present review was to assess the potential of nano and micro emulsions for the delivery of antidepressant and anxiolytic drugs. The results from several studies showed that nanometric emulsions were able to increase drug strength up to 20,270-fold (compared to aqueous solubility). Moreover, in general, the formulations showed droplet size, polydispersity index, zeta potential, viscosity, osmolality, pH, in vitro drug release and ex vivo drug permeation as adequate for the intended effect and administration route. In vivo animal pharmacokinetic experiments showed that nanometric emulsions improved systemic drug bioavailability and/or brain targeting, and in vivo pharmacodynamic studies showed that they had antidepressant and/or anxiolytic effects, also being apparently safe. Hence, the current review provides proof of the potential of nano and microemulsions for improving solubilization and increasing the overall bioavailability of antidepressant and/or anxiolytic drugs, providing evidence of a possible useful strategy for future therapies.